Acute Effects of an Afterschool Running and Reading Program on Executive Functioning in Children: An Exploratory Study - Jeffrey D. Graham; Emily Bremer; Chloe Bedard; Pallavi Dutta; Michelle Ogrodnik; John Cairney (Frontiers Media S.A., 2020)
Objective: Emerging research within school settings suggests acute forms of physical activity and exercise lead to improvements in executive functioning among children. However, research pertaining to these effects within the afterschool setting remains limited. The primary purpose of this study was to investigate the acute effects of a community-based afterschool running and reading program on executive functioning in 8 to 12-year-old children.Method: Fifty participants were initially recruited to participate in this study. However, due to the COVID-19 pandemic, data collection was terminated prematurely which resulted in a sample size of 15 participants. Participants (N = 10) from School 1 completed two batteries of executive function assessments (i.e., inhibition, switching, and updating) separated by 15-min of running or 15-min of sedentary reading. Whereas, only 5 participants from School 2 completed assessments of executive functioning prior to and following the running portion of the program (due to the early termination of data collection).Results: Overall, executive function scores improved across each assessment following the running condition when compared to the reading condition (School 1). Inhibition scores significantly improved, and these effects were very large (School 1). Across both schools, improvements in executive functioning following the running portion of the program ranged from small-large in effect size.Conclusion: Findings from the present study provide initial evidence for the acute effects of a community-based afterschool running and reading program on executive functioning in children. Future research with larger samples in afterschool settings is recommended to replicate this preliminary work.